Clinical and hormonal characteristics and growth data of 45,X/46,XY mosaicism in 38 Chinese patients - Yang, Jiaoru; Li, Yan; Li, Pin (Frontiers in Pediatrics, 2023)
Backgrounds:45,X/46,XY mosaicism is the most common type of sex chromosomal abnormality in disorders of sex development (DSD). We investigated the clinical manifestations, serum sex hormone levels and growth data of 38 45,X/46,XY mosaicism patients, which provides better insight into this disease. Results: Among the 38 cases of 45,X/46,XY mosaicism, 18 cases showed a female external genitalia phenotype (the female group) with an external masculinization score (EMS) of 1 (0 3) [median (range)], and 20 cases showed a male external genitalia phenotype (the male group) with an EMS of 7.63 (3 11) [median (range)]. The age at diagnosis ranged from 0.7 to 16.1 years. Under 2 years of age, the standard deviation scores of height (HtSDS) were in the normal range and then they gradually decreased. The inhibin B (INHB), anti‑Mullerian hormone (AMH), and testosterone (T) levels after human chorionic gonadotropin (HCG) stimulation and the T:DHT ratio in the male group were significantly higher than those in the female group (P<0.001). The basal luteinizing hormone (LH), basal follicle-stimulating hormone (FSH), peak LH and peak FSH in females were significantly higher than those in males (P<0.05). Their height showed a positive correlation with T levels after HCG stimulation (r=0.636, P<0.01), T:DHT ratio (r=0.724, P<0.01), growth hormone (GH) (r=0.827, P<0.05), and insulin-like growth factor 1 (IGF-1) (r = 0.067, P > 0.05) and a negative correlation with gonadal pathology in ovarian tissue (r=-0.663, P<0.05) and the number of chimaeric XY cells (r=-0.533, P<0.05). Conclusions: Patients with 45,X/46,XY mosaicism have specific growth patterns. Their HtSDS was in the normal range during 0-2 years of age and then they began to show a short stature after 2 years of age. The probability of short stature in females was higher than that in males. WtSDS were all in the normal range, but below the median. BMISDS was in the normal range, and there was no evidence of obesity. The gonads in the male group retained a certain androgen secretion function, while the gonadal damage is more severe in the female group.